Approach to Public Expenditure Management and the Effect of Treasury Single Accounts System on Public University Adminstration: A CASE STUDY OF NORTH CENTRAL UNIVERSITIES IN NIGERIA - Otse, Amos (The Journal of Accounting and Management, 2021)
Treasury Single Account (TSA) is an intervention policy of government that will drive revenue generation and close leakages of waste of fund in Nigeria. To achieve the goals of TSA, a unified banking structure that allows for funds and spending to be centralized by government was introduced. The study examined the effect of TSA on the Nigerian Universities to ascertain efficiency, level of acceptability to the universities and the implication of the policy to the autonomy of the universities. The study used primary data from questionnaire and it is limited to the universities in the north central geopolitical zone of Nigeria. The study employed a reconnoiter survey to identify and examine the changes in approach to public expenditure management as a result of the introduction of the TSA and its acceptability in the universities in Nigeria. A performance ratio analysis method was used to establish the change level. The findings shows that there was no significant change in value to the administration of the universities, university autonomy was eroded, bureaucratic bottlenecks increased, excess power to the CBN and too many interests on oversight functions. The study recommend improvement on TSA policy to help build efficiency in budget and performance of the public universities in Nigeria.